Evaluation of Correlation between the in Vitro Susceptibility of Field Isolates of Leishmania major and Clinical Outcomes of Meglumine Antimoniate Therapy in Fars Province, Iran - Nafiseh Ghobakhloo; Mohammad Hossein Motazedian; Behrad Pourmohammadi; Zahra Yousefi (Tehran University of Medical Sciences, 2017)
Background: This study was designed to detect whether there is a correlation between in vitro susceptibility of field isolates of Leishmania major and the clinical outcomes of meglumine antimoniate (Glucantime®) therapy, the mainstay of cutaneous leishmaniasis treatment in Iran. Methods: Forty-three patients infected with L. major were enrolled in this study from October 2009 to March 2010 and categorized as responsive or unresponsive to Glucantime® treatment after receiving the appropriate therapy. Then, intracellular amastigote approach was conducted on these field strains to investigate in vitro drug susceptibility as well. Results: At clinical level, out of 43 patients, 15 were clinically non-responsive and 28 were responsive to antimony therapy. All those 28 clinically sensitive strains were susceptible to antimony in the in vitro assay, whereas merely 11 isolates from 15 non-healing isolates were resistant in vitro. Finally, a good correlation (78.9%) with high sensitivity, specificity (100/73) between clinical outcomes and the in vitro susceptibility test was achieved.  Conclusion: The intracellular amastigote model could be an appropriate assay for evaluation of the in vivo drug sensitivity of field isolates. However, more comprehensive studies with larger sets of isolates are needed to confirm these preliminary data.